Deteksi Kesehatan Keuangan Badan Usaha Milik Negara (BUMN) Menggunakan Financial Discriminant Models - Iqbal, Achmad; BR. P, Sofia Asyriana (Jurnal ASET (Akuntansi Riset), 2020)
State-owned enterprises (BUMN) are business entities that are not only responsible for profit creation but also as a source of state revenue. This study aims to detect the financial health of BUMN using Financial Discriminant Models, namely the Springate and Taffler Models. The analysis was carried out on the BUMN financial reports for the 2014-2018 period of 16 companies with 80 financial reports being analyzed. The results of this study show that by using the Springate Model, it is known that 2017 is the best year, no BUMN is experiencing financial distress. 2018 was the worst year with 12 BUMNs declared financial distress and only 4 companies categorized as healthy. The results of the analysis with the Taffler Model show that in 2014 all BUMNs were categorized as healthy and only 1 company was declared to have financial distress.Â